Psychological Adaptation: Taking Hold of Post Sectio Caesarian Primiparous Mother - Emmelia Astika Fitri Damayanti; Tety Mulyati Arofi (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2022)
Background: Primiparous mothers after SC surgery need support from their families and health workers, especially in adapting to their new roles. The mother will feel worried about her inability and sense of responsibility in caring for her baby. Mothers who cannot adapt well can be at risk of experiencing postpartum blues to postpartum depression. Objectives: The purpose of this study is to describe the experience of psychological adaptation: taking hold of post SC primiparous mothers. Methods: This study is a qualitative study with a phenomenological approach. The research sample was taken by purposive sampling, namely primiparous mothers after SC surgery as many as 10 mothers. Data collection is based on interview guidelines and observation notes. Results: The results showed that all mothers (100%) had never been taught breast care and oxytocin massage during hospitalization; 7 mothers (70%) had little milk production; 8 mothers (80%) mastered breastfeeding techniques; all mothers (100%) were not ready to take care of their own babies; 5 mothers (50%) feel anxious; 8 mothers (80%) experienced changes in sleep patterns; all mothers (100%) did early mobilization; all mothers (100%) received support from their husbands and families Conclusion: Primiparous mothers have no previous experience so they need support from health workers and families in achieving their new role as mothers. Health workers are expected to provide support in the form of education and counseling, especially to primiparous mothers about the problems experienced by mothers during the postpartum period.